2019
DOI: 10.24252/minds.v6i2.9503
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of E-Trust and E-Service Quality to E-Loyalty with E-Satisfaction as the Mediation Variable (The Study of Bebas Bayar Application User’s in Indonesian)

Abstract: This research aims to examine the effect of e-trust and e-service quality on e-loyalty of Bebas Bayar application with e-satisfaction as a mediation variable. This study used a non-probability sampling of 220 respondents and path-analysis. The results of this study show that all proposed variable hypotheses are significant, but e-service quality has no significant influence o n e-loyalty. E-trust and e-service quality have a significant effect on e-loyalty with e-satisfaction as a mediation variable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 10 publications
4
16
0
2
Order By: Relevance
“…This reseach is accordance with the results of previous research conducted by (Gotama and Indarwati, 2019;Melinda, 2017;Wyer and Mells, 2018) showing that e-service quality has no effect on e-loyalty. These researches show an insignificant effect of e-service quality in increasing e-loyalty in the context of online business.…”
Section: Effect Of E-service Quality On E-loyaltysupporting
confidence: 92%
See 1 more Smart Citation
“…This reseach is accordance with the results of previous research conducted by (Gotama and Indarwati, 2019;Melinda, 2017;Wyer and Mells, 2018) showing that e-service quality has no effect on e-loyalty. These researches show an insignificant effect of e-service quality in increasing e-loyalty in the context of online business.…”
Section: Effect Of E-service Quality On E-loyaltysupporting
confidence: 92%
“…In 2020, the number of OVO users decreased from 56% to 55% users (Prasetyo, 2020). This supports and triggers interest to study further regarding e-loyalty owned by OVO users There are inconsistencies in the results of previous research that produce differences (Shafiee and Bazrgan (2018); Gull, et al (2020); Khan and Zubair (2019); Gotama and Indarwati (2019); Melinda (2017); Wyer and Mells (2018)), being an interesting research gap for further research on how the actual effect of e-service quality on e-loyalty and to overcome the research gap found, this research included mediating variables to bridge the research gap. To close the research gap in this research, e-trust and brand image mediation variables were included.…”
Section: Introductionmentioning
confidence: 62%
“…In the modified TAM model, several elements are used by attributes in a website that can increase customer trust and also the convenience and security factors in using online-based transactions. Other research conducted by (Gotama & Indarwati, 2019), (Kasih & Moeliono, 2020), and (Juwaini et al, 2022) also states that there is an influence between trust and loyalty mediated by satisfaction.…”
Section: Introductionmentioning
confidence: 87%
“…Research that has previously been reviewed by Tobagus (2018), Hidayah & Utami (2017), Haria & Mulyandi (2019) and Fitriani (2018) proves that e-service quality has a significant positive effect on e-satisfaction and is contrary to Gotama & Indarwati (2019) dan Suprapti & Suparmi (2020) which shows the results that e-service quality has no effect on esatisfaction. Then the previous research that has been reviewed by Irwansyah & Mappadeceng (2018), Ashoer et al (2019), Prasmara et al (2020), Sativa (2016), Hendika et al (2011), Nasution et al (2019, Magdalena & Jaolis (2018), Riza & Sutopo (2017), and Budiman et al (2020) proves that e-service quality has a significant positive effect on eloyalty and is contrary to Syafiq & Haryono (2010), Komara (2013), Wulandari (2017), Pudjarti et al (2019) and Melinda (2017) which shows the results that e-service quality has no effect on e-loyalty.…”
Section: Introductionmentioning
confidence: 94%